2021
DOI: 10.1021/acs.jafc.1c02124
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex-Competitive ELISA for Detection and Characterization of Gluten during Yogurt Fermentation: Effects of Changes in Certain Fermentation Conditions on Gluten Protein Profiles and Method Reproducibility Assessment

Abstract: The protein/peptide profiles of gluten during yogurt fermentation were evaluated using an optimized multiplexcompetitive ELISA by preparing yogurts incurred with gluten at different concentrations and by varying certain fermentation conditions. Analysis indicated that epitope-specific responses with antibody binding to glutenin epitopes decreased less during longer fermentation times or at higher starter culture concentrations relative to gliadins. Incomplete proteolysis was observed after 24 h of fermentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Multiplex-competitive ELISA was performed as described previously. , Briefly, 10 μg/mL gluten was coated onto microtiter plates, and the plates were incubated overnight at 4 °C. The plates were then washed (4 times with PBST) and blocked with NFDM (37 °C for 1 h).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiplex-competitive ELISA was performed as described previously. , Briefly, 10 μg/mL gluten was coated onto microtiter plates, and the plates were incubated overnight at 4 °C. The plates were then washed (4 times with PBST) and blocked with NFDM (37 °C for 1 h).…”
Section: Methodsmentioning
confidence: 99%
“…Intact wheat gluten (G5004, Sigma-Aldrich) was used as a calibration standard in the multiplex-competitive ELISA as previously described. , The lot of gluten used in this study had a protein content of 83% (N × 5.7) as per the Certificate of Analysis. This protein content value was used when preparing the gluten standards.…”
Section: Methodsmentioning
confidence: 99%
“…Bender and Schönlechner (2020) in their review reported negative impact of protease application on sorghum bread quality in comparison with other gluten-free breads, however further studies needs to be The study highlighted that such techniques may also be exploited for sorghum to control the process parameters to achieve desired flour properties. Method for detection of gluten during each step of the bread development must also be developed, similar to the one performed for meat and pastry (Scharf et al, 2013), beer (Panda et al, 2015) and yogurt (Panda et al, 2021).…”
Section: Additivesmentioning
confidence: 99%
“…The study highlighted that such techniques may also be exploited for sorghum to control the process parameters to achieve desired flour properties. Method for detection of gluten during each step of the bread development must also be developed, similar to the one performed for meat and pastry (Scharf et al, 2013), beer (Panda et al, 2015) and yogurt (Panda et al, 2021).…”
Section: Existing Gaps Challenges and Future Prospectsmentioning
confidence: 99%
“…Consequently, the Codex Alimentarius and the European Union have designated 'glutenfree' as a gluten content of 20 ppm or less and 'very low gluten' as a gluten content of less than 100 ppm, respectively. 6,7 Despite the recent development of numerous gluten detection methods, including various enzyme-linked immunosorbent assays (ELISA) [8][9][10][11] and other sophisticated techniques, such as real-time polymerase chain reaction, 12 gel-permeation highperformance liquid chromatography with uorescence, 13 pretreatment method to improve sensing accuracy, bio-sensing pretreatment method, microarray technology, 14 lateral ow immunoassay, 15 and liquid chromatography-mass spectrometry, 16 there remains a need for cost-effective and practical in situ detection methods that do not require complex analytical instruments.…”
Section: Introductionmentioning
confidence: 99%